Enhancing Visitor Experience at The Subkoss Museum Through Historical and Cultural Education - Sustianingsih, Ira Miyarni; Susetyo, Berlian (Yayasan Keluarga Guru Mandiri, 2026)
This study explores strategies to enhance the visitor experience at the Subkoss Garuda Sriwijaya Museum through historical and cultural education. Visiting museums is essential in education, as it offers contextual learning experiences that allow visitors to understand history and culture directly through interaction with authentic local artifacts and narratives. Using a descriptive qualitative method, this research aims to analyze the role of educational initiatives in strengthening the museum's function as a public learning space. The findings reveal that contextual education, emphasizing the values of Indonesia's independence struggle and local cultural heritage, effectively enhances visitors' emotional attachment and intellectual engagement. Key innovations include the integration of interactive media, thematic guided tours, and experiential learning activities, all of which collectively create a more dynamic and meaningful museum experience. The museum also offers public programs, including history competitions, community discussions, and participatory activities, which expand educational outreach and foster social cohesion. These efforts have led to a consistent increase in visits from diverse demographic groups. This study concludes that collaboration between museum managers and stakeholders in the education sector is crucial for developing sustainable, engaging, and participatory museum programs. It contributes to the field of museology and public history by demonstrating that educational innovation can transform museums into vibrant centers of community learning and cultural preservation.